Evaluation of yogurt with enhanced cysteine content - Bala, Soumya; Schmidt, Karen A. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2014)
Amino acids are the building blocks of protein and assist with metabolism in the body. In the human body, the amino acid cysteine can be synthesized from methionine by the enzyme Υ-cystathionase. Because certain human subpopulations such as those prone to cataracts have decreased Υ-cystathionase activity, dietary cysteine may be beneficial. Nutritionally, yogurt mix is one of the best dairy food sources of methionine and cysteine, but the heat treatment used in manufacturing yogurt decreases the dietary availability of cysteine. Last year, it was shown that supplementing yogurt mixes with whey protein isolate (WPI) (>90% protein) and processing yogurt mixes at a lower temperature produced yogurts with increased cysteine. Because the quality or cysteine content of the yogurt during the expected storage life is unknown, this study was conducted to determine if a combination of WPI addition and non-optimal process conditions could produce a yogurt with higher cysteine content and an acceptable shelf life. In this study, control yogurt mixes were made with nonfat dry milk (NDM) and processed at 90oC for 7 minutes, whereas the experimental yogurt mixes were made with NDM and WPI and processed at 70oC for 20 minutes. Both mixes were cooled, inoculated, fermented into yogurt, stored at 4°C, and evaluated periodically over a 60-day period. The experimental yogurts had ~2X more cysteine than the control yogurt; this trend was present throughout storage. After 60 days of storage, the water-holding capacity (WHC) and firmness was greater and the syneresis was less for the experimental yogurt than the control yogurt. These results show that yogurt supplemented with WPI and processed at less optimal conditions may be a good source of the conditional amino acid cysteine during storage.
Dairy Research, 2012 is known as Dairy Day, 2012
Keywords: Yogurt; Whey protein isolate; Cysteine